Population Based Paternity Rate and Partner Birth Outcomes Among Utah Men With Inflammatory Bowel Disease. (November 2017) - Martin, Luke; Peche, William; Peterson, Kathryn; Wan, Yuan; Chan, Stephanie; Morton, Ryan; Zhang, Chong; Presson, Angela P; Hotaling, James
Abstract : OBJECTIVES: Crohn's disease (CD) and ulcerative colitis (UC) impact an estimated 350, 000 reproductive age men in the United States. The reproductive consequences are largely unknown. The objective of this study was to evaluate the effects of CD and UC on reproductive outcomes. METHODS: From the Utah Population Database, we identified a cohort of male patients with CD (1, 245) and UC (1, 368). Male‐sibling controls were identified, and birth outcome data from offspring were obtained. Analyses for CD and UC were completed separately. RESULTS: Among UC patients (473) with at least one male sibling (1, 020), 66% had offspring, which was not different compared with siblings (61%, P =0.16). Birth outcomes were not different between UC patients and male siblings: congenital malformations (UC 6% vs. 6%, P =0.99), perinatal complications (UC 35% vs. 31%, P =0.23), mean birth weight (UC 3, 347 vs. 3, 357 g, P =0.53), mean length of gestation (UC 39.0 vs. 39.1 weeks, P =0.54). Among CD patients (421) with at least one male sibling (833), 58% had offspring, which did not differ compared with siblings (57%, P =0.77). Similarly, there were no differences in partner birth outcomes: congenital malformations (CD 7% vs. 6%, P =0.27), perinatal complications (CD 35% vs. 32%, P =0.12), mean birth weight (CD 3, 276 vs. 3, 324 g, P =0.13), or mean length of gestation (38.8 vs. 39 weeks, P =0.24). CONCLUSIONS: We found no differences in paternity rate or female partner birth outcomes in Utah men with UC or CD compared with male‐sibling controls. UC and CD do not appear to affect the reproductive outcomes of men in Utah.